2015
DOI: 10.1371/journal.pone.0116473
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synaptosomal Proteins Binding to Monomeric and Oligomeric α-Synuclein

Abstract: Monomeric α-synuclein (αSN) species are abundant in nerve terminals where they are hypothesized to play a physiological role related to synaptic vesicle turn-over. In Parkinson’s disease (PD) and dementia with Lewy body (DLB), αSN accumulates as aggregated soluble oligomers in terminals, axons and the somatodendritic compartment and insoluble filaments in Lewy inclusions and Lewy neurites. The autosomal dominant heritability associated to mutations in the αSN gene suggest a gain of function associated to aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 73 publications
(95 reference statements)
10
98
0
Order By: Relevance
“…We hypothesised that aggregated AS binds directly to and stimulates the predominant Ca 2+ pumps in the plasma membrane and endoplasmic reticulum, PMCA and SERCA, because total AS levels remain fairly stable in our cell models and the decrease in cytosolic Ca 2+ is prevented by the aggregation inhibitor ASI-1D. Co-immunoprecipitation experiments followed by proteomic techniques have demonstrated that PMCA from porcine brain binds both monomer and oligomeric AS [20]. Likewise, SERCA was found to bind AS by pull-down experiments; however, pronounced selectivity was seen with strong binding of aggregated AS to SERCA in contrast to very low binding of monomeric AS.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesised that aggregated AS binds directly to and stimulates the predominant Ca 2+ pumps in the plasma membrane and endoplasmic reticulum, PMCA and SERCA, because total AS levels remain fairly stable in our cell models and the decrease in cytosolic Ca 2+ is prevented by the aggregation inhibitor ASI-1D. Co-immunoprecipitation experiments followed by proteomic techniques have demonstrated that PMCA from porcine brain binds both monomer and oligomeric AS [20]. Likewise, SERCA was found to bind AS by pull-down experiments; however, pronounced selectivity was seen with strong binding of aggregated AS to SERCA in contrast to very low binding of monomeric AS.…”
Section: Discussionmentioning
confidence: 97%
“…We successfully cross-linked α-syn oligomers using FA, thereby increasing stability towards SDS and urea denaturation. This oligomer preparation binds neuronal proteins in a conformational specific manner [21, 22], and also bind the two conformational specific antibodies FILA and MJF14. The FA mediated crosslinking did not disturb the overall twisted ribbon-like oligomeric structure, the size of the oligomers, their antigenicity toward FILA and MJF14 or the crosslinked oligomers applicability as calibrators in an α-syn oligomer specific ELISA assay [23].…”
Section: Discussionmentioning
confidence: 99%
“…Production of α-syn and α-syn oligomers was performed as previously described [19, 21, 32]. In short, purified α-syn was dissolved in PBS to a final concentration of 10mg/mL and incubated on ice for 30 minutes while vortexed regularly.…”
Section: Methodsmentioning
confidence: 99%
“…potentially pathogenic, a‐synuclein (Betzer et al . ). Again, label‐free quantification was used and, interestingly, there were fewer proteins that specifically interacted with monomeric compared to oligomeric a‐synuclein.…”
Section: Interaction Proteomicsmentioning
confidence: 97%